Intimate partner violence and its association with maternal depressive symptoms 6-8 months after childbirth in rural Bangladesh - Kabir, Zarina N; Nasreen, Hashima E; Edhborg, Maigun (Co-Action Publishing, 2014)
Background: Intimate partner violence (IPV) is important to be addressed simply because it is a gross violation of human rights. Its prevalence is wide ranging across the world, with higher prevalence reported in low- and middle-income countries. Evidence shows that IPV has both direct and indirect impact on women’s health, mainly related to physical health. Little is known of impact of IPV on mental health of women, particularly after childbirth. Objective: To describe the prevalence of intimate partner violence (IPV) experienced by women 6-8 months after childbirth, and the factors associated with IPV. The study also aims to investigate the association between IPV and maternal depressive symptoms after childbirth. Design: The study used cross-sectional data at 6-8months postpartum. The sample included 660 mothers of newborn children. IPV was assessed by physical, emotional, and sexual violence. The Edinburg Postnatal Depression Scale assessed maternal depressive symptoms. Results: Majority of the women reported experiencing intimate partner violence categorised as physical (52%), sexual (65%) and emotional (84%) violence by spouse. Husband’s education (OR: 0.41, CI: 0.23-0.73), poor relationship with husband (OR: 2.64, CI: 1.07-6.54) and emotional violence by spouse (OR: 1.58, CI: 1.35-1.83) were significantly associated with physical IPV experienced by women. Having a fussy and difficult child (OR: 1.05, CI: 1.02-1.08), poor relationship with husband (OR: 4.95, CI: 2.55-9.62) and experience of physical IPV (OR: 2.83, CI: 1.72-4.64) were found to be significant predictors of maternal depressive symptoms amongst women 6-8 months after childbirth. Neither forced sex nor emotional violence by intimate partner was found to be significantly associated with maternal depressive symptoms 6-8 months after childbirth. Conclusion: It is important to screen for both IPV and depressive symptoms during pregnancy and postpartum. Since IPV and spousal relationships are the most important predictors of maternal depressive symptoms in this study, couple-focused intervention at the community level are suggested.